2022
DOI: 10.3389/fnhum.2022.859538
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Functional Connectivity in the Default Mode Network Differentiates the Combined and Inattentive Attention Deficit Hyperactivity Disorder Types

Abstract: Neuroimaging studies have revealed neurobiological differences in ADHD, particularly studies examining connectivity disruption and anatomical network organization. However, the underlying pathophysiology of ADHD types remains elusive as it is unclear whether dysfunctional network connections characterize the underlying clinical symptoms distinguishing ADHD types. Here, we investigated intrinsic functional network connectivity to identify neural signatures that differentiate the combined (ADHD-C) and inattentiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Children with ADHD have been reported to have aberrant structural connectivity predominantly in fronto-striatal connections and other tracts connecting parietal, temporal, and left occipital regions [ 87 , 88 ]. Moreover, disruptions in functional connections have been demonstrated in the FPN, DMN, DAN, and visual network, and prior cross-sectional studies [ 76 , 80 , 89 91 ], and our recent longitudinal study has reported age-related differences in functional connections between various higher-order cognitive networks [ 35 ]. Previous studies demonstrating aberrant functional and structural connections in DMN, SAL, DAN, and visual network have suggested that this could be the reason for deficits in attention, impulsivity, and executive functions in children with ADHD [ 79 , 92 – 94 ].…”
Section: Discussionmentioning
confidence: 71%
“…Children with ADHD have been reported to have aberrant structural connectivity predominantly in fronto-striatal connections and other tracts connecting parietal, temporal, and left occipital regions [ 87 , 88 ]. Moreover, disruptions in functional connections have been demonstrated in the FPN, DMN, DAN, and visual network, and prior cross-sectional studies [ 76 , 80 , 89 91 ], and our recent longitudinal study has reported age-related differences in functional connections between various higher-order cognitive networks [ 35 ]. Previous studies demonstrating aberrant functional and structural connections in DMN, SAL, DAN, and visual network have suggested that this could be the reason for deficits in attention, impulsivity, and executive functions in children with ADHD [ 79 , 92 – 94 ].…”
Section: Discussionmentioning
confidence: 71%